Soil capacitance sensors and stem dendrometers. Useful tools for irrigation scheduling of commercial orchards? - Ferrer, P.; Castel, J. R.; Intrigliolo, D. S. (Spanish Journal of Agricultural Research, 2010)
Irrigation scheduling is often performed based on a soil water balance, where orchard evapotranspiration is estimated using the reference evapotranspiration (ETo) times the crop coefficient (Kc). This procedure, despite being widely spread, has some uncertainties. Because of this, plant and soil water status monitoring could be alternatively or complementarily used to schedule irrigation. The usefulness of capacitance probes was evaluated during several seasons in large irrigation districts where irrigation practices were changed over years from the ETo * Kc model to the analysis of soil water status trend. This area corresponds to drip irrigated orchards planted with citrus, peach, nectarine and persimmon. Around 25% less irrigation was applied with no substantial yield penalty when the information provided by capacitance probes was correctly applied for irrigation management. On the other hand, the usefulness of stem dendrometers for continuously monitoring plant water status was evaluated in a young plum experimental orchard. Over two years, irrigation was scheduled using exclusively trunk shrinkage via the signal intensity approach by means of a baseline equation previously obtained in the orchard. Results showed that it was not always possible to schedule irrigation based on the trunk shrinkage signal intensity due to the temporal changes in the reference values that occurred as trees aged. Overall, results obtained are discussed in terms of the possible extrapolation at field level of both capacitance probes and stem dendrometers. Advantages and drawbacks of each technique are analyzed and discussed.